Reckless Henry Kissinger and the tragedy of Vietnam - Brigham, Robert K. (Robert Kendall) 1960 (PublicAffairs, 2018)
"This disturbing new account of Henry Kissinger's Vietnam years shows a blundering, self-serving man who led America to tragedy and Vietnam to waste in an unnecessarily dragged-out, ill-conceived war"--